MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN TWO STAY-TWO STRAY - SAPTO NUGROHO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to increase students' motivation to learn mathematics in class XII MIPA 6 SMA Negeri 5 Yogyakarta for the academic year 2020-2021 through the Type Two Stay-Two Stray Cooperative Learning Model and to find out the responses of class XII MIPA 6 students at SMA Negeri 5 Yogyakarta in the academic year 2020-2021. on the implementation of learning with the Two Stay-Two Stray Type Cooperative Model. This research is a Classroom Action Research conducted collaboratively with mathematics teachers with specialization in class XII SMA Negeri 5 Yogyakarta and the research subjects are students of class XII MIPA 6 SMA Negeri 5 Yogyakarta in the academic year 2020- 2021 as many as 36 students. The instruments used in this study include observation sheets on the implementation of learning, questionnaires on students' mathematics learning motivation, end-of-cycle test questions, field notes, and learning documents. students towards the implementation of learning with the Type Two Stay-Two Stray Cooperative Model, end-of-cycle tests, preparation of field notes, and learning documentation. Based on the results of the questionnaire on students' motivation to learn mathematics, it is known that 84.4% of the 32 students in class XII MIPA 6 SMA Negeri 5 Yogyakarta in the 2020-2021 academic year experienced an increase in their motivation to learn mathematics from cycle I to cycle II. The increasing motivation of students in learning mathematics is accompanied by an increase in the number of students who complete learning. The results of the end-of-cycle test showed that the number of students who had completed learning mathematics experienced a significant increase from cycle I to cycle II, from 68.6% in the first cycle to 93.8% in the second cycle from 32 students in XII MIPA. 6 SMA Negeri 5 Yogyakarta for the academic year 2020-2021 ABSTRAKPenelitian ini bertujuan untuk meningkatkan motivasi belajar matematika siswa kelas XII MIPA 6 SMA Negeri 5 Yogyakarta tahun pelajaran 2020-2021 melalui Model Pembelajaran Kooperatif Tipe Two Stay-Two Stray dan untuk mengetahui respon siswa kelas XII MIPA 6 SMA Negeri 5 Yogyakarta tahun pelajaran 2020-2021 terhadap pelaksanaan pembelajaran dengan Model Kooperatif Tipe Two Stay-Two Stray.Penelitian ini merupakan Penelitian Tindakan Kelas yang dilakukan secara kolaboratif dengan guru matematika peminatan kelas XII SMA Negeri 5 Yogyakarta dan subyek penelitian yaitu siswa kelas XII MIPA 6 SMA Negeri 5 Yogyakarta tahun pelajaran 2020-2021 sebanyak 36 siswa. Instrumen yang digunakan dalam penelitian ini meliputi lembar observasi pelaksanaan pembelajaran, angket motivasi belajar matematika siswa, soal tes akhir siklus, catatan lapangan, dan dokumen pembelajaran. siswa terhadap pelaksanaan pembelajaran dengan Model Kooperatif Tipe Two Stay-Two Stray, tes akhir siklus, penyusunan catatan lapangan, dan dokumentasi pembelajaran. Berdasarkan hasil angket motivasi belajar matematika siswa yang telah diperoleh, diketahui bahwa 84,4 % dari 32 siswa yang ada di kelas XII MIPA 6 SMA Negeri 5 Yogyakarta tahun pelajaran 2020-2021 mengalami peningkatan motivasi belajar matematika dari siklus I ke siklus II. Meningkatnya motivasi siswa dalam belajar matematika diiringi oleh meningkatnya banyak siswa yang tuntas dalam belajar. Hasil tes akhir siklus menunjukkan bahwa banyaknya siswa yang tuntas dalam belajar matematika mengalami peningkatan yang cukup besar dari siklus I ke siklus II, yaitu dari 68,6 % pada siklus I menjadi 93,8 % pada siklus II dari 32 siswa yang ada di XII MIPA 6 SMA Negeri 5 Yogyakarta tahun pelajaran 2020-2021